Quantitative Estimation of Yeast on Maxillary Denture in Patients with Denture Stomatitis and the Effect of Chlorhexidine Gluconate in Reduction of Yeast - Jaykumar R Gade; Vandana Gade (Wolters Kluwer Medknow Publications, 2011)
Denture stomatitis is a condition associated with wearing of a denture. The predisposing factor leading to denture stomatitis could be poor oral hygiene, ill-fitting denture and relief areas. Around 30 patients with denture stomatitis were advised to rinse with chlorhexidine gluconate mouthwash for 14 days and were directed to immerse the upper denture in the chlorhexidine solution for 8 hours. The samples were collected by scraping maxillary denture in saline at three intervals, prior to, at the end of 24 hours and after 14 days of treatment, then were inoculated and quantitative estimation of the yeast growth on Sabouraud's dextrose agar plate was done. It was observed that after a period of 14 days, there was a reduction in the growth of yeast and also improvement in the clinical picture of the oral mucosa